Destination brand image of Western Australia's South-West Region: Perceptions of local versus international tourists - Quintal, Vanessa; Phau, Ian; Polczynski, Aleksandra (Sage Publications Ltd., 2014)
This article explores whether a destination brand image exists in Western Australia’s (WA) South-West region, and whether local and international visitors hold different perceptions of it. A questionnaire using a non-probability convenience sampling method was self-administered to students from a university in WA. From the 228 useable survey responses collected, differences were observed between the perceptions of local and international visitors. In-group approval played a significantly higher role in influencing destination choice for international visitors. Five factors were derived from the brand image of WA’s South-West region. The article highlights the need for researchers and practitioners to identify both the most salient and the least salient aspects of a destination in order to address what drives and inhibits destination choice. Examining perceptual differences between local and international visitors will help to identify the differential impacts of cultural perceptions on satisfaction and repeat visitation to the destination.